486 Patients Who Die, Then Talk: Outcomes in Patients with Traumatic Extra-Arachnoid Subdural Hematoma. (1st April 2022) - Eaton, Jessica C.; Meyer, R. Michael; Greil, Madeline; Young, Christopher C.; Temkin, Nancy; Barber, Jason; Bonow, Robert H.; Chesnut, Randall M.
Abstract : INTRODUCTION: A critical step in the management of TBI patients is evaluating for lesions that require urgent surgical evacuation. Amongst the most common of these surgical lesions are subdural hematomas (SDH). A subset of patients with SDH have purely extra-arachnoid lesions (EASDH). These patients present in similarly grave neurologic condition as the general SDH hematoma population. METHODS: This is a single-center prospective cohort of patients presenting with EASDH from January 2015 to December 2016. The senior author, an neurosurgical trauma subspecialist, made the determination of EASDH versus mixed subarachnoid and SDH based on the patient's CT scan. Controls from the TRACK-TBI database who had SDH as well as either subarachnoid or other parenchymal injuries were included. RESULTS: A total of 49 patients with EASDH were compared to 246 controls. There were no significant differences in baseline demographics between the groups. A significant difference in midline shift was noted. After controlling for midline shift, EASDH patients had 5.68 greater odds of having a better 2-week GOS-E. The expected two-week mortality, as predicted by the CRASH model, was similar between the two groups, but the EASDH group fared much better than the predicted mortality, at 10%. CONCLUSION: Patients with EASDH represent a unique clinical entity. They are often elderly and have large lesions with significant midline shift. However, patients often have a dramatic improvement.